2022
DOI: 10.14744/tjtes.2022.22796
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Injuries and Deaths by Trauma Scores due to Occupational Accidents

Abstract: BACKGROUND: This study was aimed to evaluate the injury characteristics, causes, results, and hospital charges in cases of occupational accidents that were reported to judicial authorities using trauma scores. METHODS: The study was performed after obtaining permission from the judicial authorities and approval from the local ethics committee. All occupational accident cases that were reported to the judicial authorities in Bolu Province between 2015 and 2019 were inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
1
0
1
Order By: Relevance
“…For instance, among workers in the state of Bahia, the MAoD was 38.9 years for individuals of Brown race, 39.4 for Black individuals, and 40.6 for White individuals 41 . Similarly, a study among Iranian workers found MAoD of 36 years, which was higher than that among Turkish workers, who had MAoD of 34 years 40,49 . Mortality from non-communicable chronic diseases related to work, such as cancers and kidney diseases, typically have higher average age at death than liver disease-related deaths 50,51 .…”
Section: Discussionmentioning
confidence: 86%
“…For instance, among workers in the state of Bahia, the MAoD was 38.9 years for individuals of Brown race, 39.4 for Black individuals, and 40.6 for White individuals 41 . Similarly, a study among Iranian workers found MAoD of 36 years, which was higher than that among Turkish workers, who had MAoD of 34 years 40,49 . Mortality from non-communicable chronic diseases related to work, such as cancers and kidney diseases, typically have higher average age at death than liver disease-related deaths 50,51 .…”
Section: Discussionmentioning
confidence: 86%
“…Um ponto relevante a ser considerado é que os acidentes de trabalho podem resultar em invalidez temporária, invalidez permanente, impacto psicológico e até a morte do indivíduo, sendo a maioria dos incidentes considerados evitáveis (DE et al, 2021;ERDEM HÖSÜKLER, 2022). Assim, fica evidente que as lesões e mortes relacionadas ao trabalho são um problema de saúde pública (ERDEM HÖSÜKLER, 2022).…”
Section: Introductionunclassified